AQUATIC FITNESS FOR PEOPLE WITH DISABILITIES LEVEL 3, PHYSICAL EDUCATION AND PSYCHOLOGY - AAEFP - Barros Gama, Cleotemberg; Bittencourt Saraiva, Waslany (Revista Gênero e Interdisciplinaridade, 2023)
The present work describes the results of the Aquatic Adaptation program for people with Disabilities level 3. The project was applied by the authors in the pool of the Association of Parents and Friends of the Exceptional - APAE Manaus, year 2019. It was idealized and applied, with a descriptive objective, having as instruments of data collection practical evaluation forms, family interview and comparative analysis, followed by data analysis and bibliographic research. As a result, allow us to know and adapt to activities aimed at quality of life, survival in the liquid environment, awareness, safety, attention, concentration, sequences of rules and limits in the cognitive, affective, motor, social areas. strategies of the Aquatic Adequacy programs for people with disabilities level 3, Physical Education and Psychology. The program offered 3 evaluations, being: initial, half-yearly and final at twelve months. It is concluded that the procedures led students to learn new behaviors, overcoming their specific difficulties, enabling new learning, benefiting quality of life, survival in the liquid environment, awareness, safety, attention, concentration, sequences of rules and limits in the cognitive areas, motor and social affective of students with disabilities level 3.